Implementasi Gugatan Sederhana Sebagai Upaya Penyelesaian Hukum Perdata Pada Wanprestasi - Mochammad Rozzano Azza (JURNAL ILMIAH NUSANTARA, 2024)
One aspect of fulfilling needs cannot be denied that the interests of each party are regulated in civil law, namely contracts which, if violated, are called defaults. Defaults with a loss value of not more than IDR 500,000,000.00 (five hundred million rupiahs) can be resolved with a simple lawsuit so that in this writing we discuss the implementation of a simple lawsuit in settlement of default cases. This writing uses the descriptive normative method. The results of the research show that the implementation of a simple lawsuit system has been tried by Perma Number 4 of 2019 concerning Amendments to Perma Number 5 of 2015 concerning Procedures for Settlement of Simple Claims even though in practice the application of a simple lawsuit system in terms of the aspect of case criteria and procedures still has good obstacles internal or external.